Cross-sectional study to assess the healthcare professionals' knowledge, attitude and practices about probiotics use in Pakistan. Issue 7 (28th July 2021) - Arshad, Muhammad Subhan; Saqlain, Muhammad; Majeed, Abdul; Imran, Imran; Saeed, Hamid; Saleem, Muhammad Usman; Abrar, Muhammad Asad; Islam, Muhammad; Hashmi, Furqan; Akbar, Muqarrab; Chaudhry, Muhammad Omer; Ramzan, Basit; et al.
Abstract : Objectives: The study aimed to assess the knowledge, attitude and practices (KAP) of HCPs regarding the use of probiotics in different health conditions and to identify various barriers that are associated with their use. Methods: A cross-sectional study was conducted on 405 HCPs by using a validated self- administered questionnaire for assessing their KAP towards probiotic use. The study data were analysed using descriptive statistics, χ 2 test and binary logistic regression (BLR). Results: Among the 405 participants, only 15.1 % of HCPs had good knowledge, while 15.6% had acceptable practices and 89.1% had a positive attitude towards probiotics. The professional position of HCPs was significantly associated with knowledge (p=0.001) and practice (p=0.001). Among all the HCPs, the pharmacists showed a significant association with good knowledge (p=0.016) and good practices (p=0.024) by using BLR. The lack of knowledge about probiotics was a major barrier to the utilisation of probiotics. Conclusions: The poor knowledge and practices regarding the use of probiotics have been seen in the current study. While the participants showed a positive attitude towards the utilisation of probiotics. To transform HCPs' positive attitude to their practices and to create awareness regarding probiotic use focused training programmes should be initiated by professional health organisations.